2015
DOI: 10.1038/ng.3442
|View full text |Cite
|
Sign up to set email alerts
|

The mutational landscape of cutaneous T cell lymphoma and Sézary syndrome

Abstract: Sézary syndrome is a leukemic and aggressive form of cutaneous T-cell lymphoma (CTCL) resulting from the malignant transformation of skin-homing central memory CD4 positive T cells. Here we performed whole-exome sequencing of tumor-normal sample pairs from 25 Sézary syndrome and 17 other CTCL patients. These analyses revealed a distinctive pattern of somatic copy number alterations in Sézary syndrome including highly prevalent chromosomal deletions involving the TP53, RB1, PTEN, DNMT3A and CDKN1B tumor suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
318
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 332 publications
(354 citation statements)
references
References 33 publications
21
318
0
9
Order By: Relevance
“…Interestingly, some of the TCR-related genes may be altered through point mutations or small indels as well as by major structural rearrangements, amplifications, and deletions. 20,23,24 Collectively, these findings strongly suggest that genetic alterations affecting TCR signaling operate as a common pathogenic mechanism in several PTCL entities.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Interestingly, some of the TCR-related genes may be altered through point mutations or small indels as well as by major structural rearrangements, amplifications, and deletions. 20,23,24 Collectively, these findings strongly suggest that genetic alterations affecting TCR signaling operate as a common pathogenic mechanism in several PTCL entities.…”
Section: Discussionmentioning
confidence: 91%
“…Ten different missense mutations spanning the coding region of PLCG1 (VF [2.1%; 38%]) were identified in 12 of 85 patients (8 AITL, 4 TFH-like PTCL; 14.1%) ( Figure 5A). Apart from previously reported variants in adult T-cell leukemia/lymphoma (ATLL) or in other PTCL, [20][21][22][23][24] we identified 2 novel variants (E730K and G869E). We generated all mutant constructs and tested their activity against WT PLCG1 in a FRET-based reporter assay of MALT1 protease activity 27,28 (Figure 5B) and in a NFAT luciferase reporter assay ( Figure 5C).…”
Section: Mutation-induced Tcr Activation In Tfh Nodal Ptcl 1493mentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8] These studies have now confirmed, expanded, and functionally validated many of the genetic aberrations detected by aCGH in MF/SS, a broad and diverse spectrum that include genes associated with T-cell receptor (TCR) signaling, activation of NF-kB, JAK/STAT signaling, chromatin remodeling, and DNA damage response. However, despite a significant degree of overlap, there was great variability in the identity and frequency of alterations at putative driver genes across studies.…”
mentioning
confidence: 72%